Effect of hydration education with whatsapp group media in increasing in fluid knowledge, fluid intake and hydration status of football athletes - Dieny, Fillah Fithra; Berlian Buntarlan, Anggia; Ratna Noer, Etika; Nissa, Choirun (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
This study aim to determine the effectiveness of WhatsApp group social media use to increase knowledge, fluid intake hydration status among football athletes. This type of research is experimental on athletes aged 15-18 years old in Bantolo football club. As many as 30 athletes were taken as sample by using consecutive sampling, divided into 3 groups. Nutritional information interventions regarding fluid regulation for athletes were given within a month by using different media for each group; PowerPoint (GPP), Whatsapp (GWA), and leaflet for control group. After the intervention there was an increase of knowledge in the GPP and the GWA. The subject has increase in fluid intake on the day before exercise, the training day and the day after. The increase in fluid intake for the training day was in the Control Group, GPP, and GWA. And after the intervention there was an increase in hydration status before training in the GPP, the GWA and in the hydration status after training there was an increase in the Control Group, the GPP, GWA. Thus, from the study, it could be concluded that Whatsapp is the most effective medium to increase nutritional knowledge and fluid intake the day before training, trainingday and day after exercise and hydration status before and after.Providing information using Whatsapp media is more effective in increasing nutritional knowledge, fluid intake and hydration status.